2014
DOI: 10.1016/j.neuron.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptors Differentially Enhance Rule Coding in Primate Prefrontal Cortex Neurons

Abstract: Flexibly applying abstract rules is a hallmark feature of executive functioning represented by prefrontal cortex (PFC) neurons. Prefrontal networks are regulated by the neuromodulator dopamine, but how dopamine modulates high-level executive functions remains elusive. In monkeys performing a rule-based decision task, we report that both dopamine D1 and D2 receptors facilitated rule coding of PFC neurons, albeit by distinct physiological mechanisms. Dopamine D1 receptor stimulation suppressed neuronal firing wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 67 publications
6
90
5
Order By: Relevance
“…The mechanisms underlying the ability of dopamine in the core of the nucleus accumbens to evoke these responses have yet to be elucidated, but the D 2 -family of receptors may be involved. Likewise, local administration into other brain areas, such as prefrontal cortical regions might specifically affect goal-tracking behavior, as dopaminergic transmission in these regions is believed to be important in mediating goal-directed behaviors [4245]. …”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the ability of dopamine in the core of the nucleus accumbens to evoke these responses have yet to be elucidated, but the D 2 -family of receptors may be involved. Likewise, local administration into other brain areas, such as prefrontal cortical regions might specifically affect goal-tracking behavior, as dopaminergic transmission in these regions is believed to be important in mediating goal-directed behaviors [4245]. …”
Section: Discussionmentioning
confidence: 99%
“…The numerosity code found in the crow endbrain is surprisingly reminiscent of findings for neurons in the monkey PFC and posterior parietal cortex (PPC) . In monkeys that discriminated visual numerosity in dot arrays (Eiselt and Nieder, 2013;Jacob and Nieder, 2014;Ott et al, 2014;Viswanathan and Nieder, 2015;Ott and Nieder, 2016;Ramirez-Cardenas et al, 2016;Nieder, 2016b), enumerated numerosity sequentially one by one in visual displays (Nieder et al, 2006), or performed hand movements (Sawamura et al, 2002(Sawamura et al, , 2010, tuned numerosity detectors were found. In the macaque PFC, neurons were also tuned supramodally to numerosity; that is, regardless of whether visual dots or acoustic sounds had to be assessed across time (Nieder, 2012).…”
Section: Labeled-line Codementioning
confidence: 99%
“…fMRI adaptation indirectly revealed peaked tuning profiles in BOLD signals in the human IPS (Piazza et al, 2004) and PFC (Jacob and Nieder, 2009). Similar to our findings in crows and monkeys, these BOLD tuning curves also showed ratio-dependent tuning widths and are best described on a logarithmic number scale.…”
Section: Labeled-line Codementioning
confidence: 99%
“…Recently, it has been shown using a task where primates either held or released a lever depending on whether a visual stimulus could be categorized as ‘greater than’ or ‘less than’ a sample stimulus of a quantity of dots that activation of different dopamine receptors in primate PFC can differentially modulate rule encoding, where D1 receptor activation increases signal to noise for neurons representing preferred rule activity, while D2 receptor activation decreases signal to noise for neurons representing a non-preferred or non-current rule(Ott et al, 2014). Taken together, this body of work has been able to identify neural correlates of rules in non-human primate PFC and has shown how these neural correlates pertain to a particular rule mostly when the rule represents a correct response option.…”
Section: Neurophysiology Of Rule Shifting In the Prefrontal Cortexmentioning
confidence: 99%
“…Further, identifying the respective roles of more precise cortical regions like the anterior cingulate cortex, prelimbic and infralimbic cortices will be important to identify what regions are responsible for what aspects of shifting rule-guided behavior. There exists some tantalizing evidence supporting a potential dissociable role for prelimbic and infralimbic cortices in mediating different aspects of flexible behavior(Rich and Shapiro, 2007, Oualian and Gisquet-Verrier, 2010), but in vivo neurophysiological experiments in conjunction with optogenetic approaches will provide more conclusive evidence. Dopamine in VS is known to be critical for flexible behavior(Haluk and Floresco, 2009).…”
Section: Future Directionsmentioning
confidence: 99%